2021
DOI: 10.1080/07853890.2021.1988695
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcal bloodstream infections in critically ill patients with COVID-19: a case series

Abstract: Background: An unexpected high prevalence of enterococcal bloodstream infection (BSI) has been observed in critically ill patients with COVID-19 in the intensive care unit (ICU). Materials and methods: The primary objective was to describe the characteristics of ICUacquired enterococcal BSI in critically ill patients with COVID-19. A secondary objective was to exploratorily assess the predictors of 30-day mortality in critically ill COVID-19 patients with ICUacquired enterococcal BSI. Results: During the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…Almost half of these enterococcal infections were caused by E. faecium [ 22 ]. This finding was in alignment with the results of observational studies from Italy reporting high prevalence of enterococcal bloodstream infections in critically ill COVID-19 patients [ 30 , 31 ]. The altered gut microbiota of SARS-CoV-2-positive individuals may be also a risk factor for pneumonia or other superinfections, as observed in other viral infections such as avian H7N9 influenza [ 32 ].…”
Section: Sars-cov-2 Infection and The Intestinal Barriersupporting
confidence: 89%
“…Almost half of these enterococcal infections were caused by E. faecium [ 22 ]. This finding was in alignment with the results of observational studies from Italy reporting high prevalence of enterococcal bloodstream infections in critically ill COVID-19 patients [ 30 , 31 ]. The altered gut microbiota of SARS-CoV-2-positive individuals may be also a risk factor for pneumonia or other superinfections, as observed in other viral infections such as avian H7N9 influenza [ 32 ].…”
Section: Sars-cov-2 Infection and The Intestinal Barriersupporting
confidence: 89%
“…Nasopharyngeal colonization with S. pneumoniae was associated with an impaired antiviral immune response in COVID-19 patients ( Mitsi et al, 2022 ), while we did not observe this in our subgroups. E. faecalis , more frequent among deceased patients than in COVID-19 negative subjects, is surprisingly a main agent of bacteremia among COVID-19 patients, particularly in ICU settings ( Giacobbe et al, 2021 ; Porto et al, 2022 ). Among the potentially protective species, we highlighted a decrease of A. muciniphila in deceased subjects when compared to those with a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on bacteremia in patients with COVID-19 [14][15][16]; however, this is the first study to compare the incidence of bacteremia between patients with COVID-19 who were treated with tocilizumab and those who were not. According to the results, tocilizumab is not an independent factor related to bacteremia in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 94%